Three-dimensional augmented reality: a transformative tool for enhancing machinery teaching and learning / Mohd Hafizz Wondi ... [et al.] - Wondi, Mohd Hafizz; Haris, Nur Izzah Nabilah; Manaf, Sharifah Raina; Sulaiman, Muhamad Nasarudin; Abu Talip, Muhamad Syukrie (Universiti Teknologi MARA, Kedah, 2023)
The subject of Mechanization of Estate Operation requires students to have a grasp of the structure of plantation machineries. Traditionally, teaching involves using 2D diagrams along with hands-on experience. However, some learning institutes lack access to real machinery. Given the complexity of these machineries, it becomes extremely difficult for students to fully understand the subject without a clear visual representation of the actual machines. Augmented reality (AR) technology offers a solution by overlaying virtual objects onto the physical environment, creating a mixed reality experience. This project aims to incorporate AR into teaching plantation machineries by developing an enhanced 3D AR teaching aid called ARyMM2.0 version 2.0. The goal is to provide students with a comprehensive learning experience. ARyMM2.0 is an upgraded version that integrates Solidworks for customizing the 3D design of machinery and UNITY application for AR implementation. While the use of AR in education is not new, its application specifically for teaching plantation machinery subject is limited. This project stands out with its integration of two digital platforms and its specific focus on AR for plantation machineries. ARyMM2.0 enhances students' learning by increasing their sense of presence, immersion, and by placing learning in an authentic environment. Being a digital tool, ARyMM2.0 can be easily shared, benefiting students who lack access to actual machinery. The project contributes to the improvement of education quality in line with SDG 4, aligns with the concept of Education 4.0, and helps students prepare for and adapt to the demands of the fourth industrial revolution (IR4.0). Although ARyMM2.0 can be commercialized as a standalone digital application, the current model that utilizes open-source platforms allows for the free sharing of knowledge with anyone in need.